Sustainable & responsible private equity in Southern Africa: evolutionary strides in a revolution? - Dhlamini, Xolisa (Research of GSB, 2018)
The study primarily explores whether private equity (PE) and venture capital (VC) firms in the Southern African Development Community (SADC) integrate sustainable and responsible investment (SRI) practices in their investment processes. Also examined were the influences, opportunities and challenges associated with Southern African PE and VC firms adopting and implementing SRI towards sustainable growth and development in the SADC region. A field study conducted with 41 PE & VC firms as well as 6 DFI's operating in the SADC region found that PE & VC firms integrated ESG factors in their investment management processes despite the majority having no formal SRI policies. ESG integration was integrated mainly for risk management and as part of the overall business strategy. Corporate governance was top of agenda followed by social and environmental aspects. Awareness for Codes for Responsible Investing in South Africa (CRISA) was very poor amongst the PE & VC firms. PE & VC firms also found little value in becoming signatories of the UNPRI. The PE & VC firms anticipated minimal or no impact to their respective businesses if ESG were to be integrated formally and consistently. PE & VC firms agreed that ESG risks should be actively managed and that the investment holding periods enable them to manage ESG effectively, however, a number of challenges hinder the integration of ESG in SADC such as difficultly in sourcing standard ESG information, translation of the information into quantitative measures, insufficient skills among professionals to assess or link ESG factors to investment performance and the lack of clear regulatory & legislative guidance in effective ESG integration. A recommendation is for PE & VC firms to formalise SRI policies as the first steps towards consistent integration of ESG in investment making processes. Further recommendations are for remuneration of PE & VC professionals to be aligned directly to ESG performance and for investors such as DFI's to be more proactive in monitoring their appointed PE & VC managers (particularly in auditing of ESG performance reports compiled by the PE & VC firms.